Analisis Pemlastis DOP dalam Resin PVC terhadap Kekuatan Tarik Alas Sandal Simetri - Ermaniardo, Yogi Dhani; Hadi, Syamsul (Politeknik Negeri Ujung Pandang, 2019)
If one side of sandals is broken, the other side cannot be used. From this problem have been made symmetry sandal which both sides are same. Then added the horizontal holes in the sandal to drain the water. The purpose of research is to mold the base of symmetry sandal and analyze the tensile strength materials. The materials are PVC resin (polyvinyl chloride, blowing agent, and black pigmen mixed with the DOP (diocthyl phthalate) or plasticizer variation and blowing agent. DOP variation used 300ml, 400ml, and 500ml in 2000g of PVC resin, 20g blowing agent, and 20g black pigmen. The material test is use tensile test for material. The research result is there is an effect of variations DOP In PVC resin on tensile strength, that tensile strength is decrease 46% from 16.20 MPa to 8.74MPa.